Working with stakeholders to reduce conflict – modelling the impact of varying hen harrier Circus cyaneus densities on red grouse Lagopus lagopus populations. Issue 5 (11th August 2014) - Elston, David A.; Spezia, Luigi; Baines, Dave; Redpath, Stephen M.; Elphick, Chris
Summary Conflict management is difficult and may benefit from scientists working closely with stakeholders. We worked with conservation and moorland management interests, to consider the potential use of a quota system to address the long‐standing conflict arising from hen harrier Circus cyaneus predation on red grouse Lagopus lagopus scoticus. We modelled the impact of different harrier densities on grouse populations using a stochastic population dynamics model to inform the debate over the consequences of a quota system. The stakeholders commissioned the work and agreed on the underlying principles, the data sets and the approach. The model covers the recovery phase from low grouse densities to a level at which driven shooting can recommence, as this phase is of paramount concern to the managers of grouse moors. The model incorporated uncertainty in parameter values as well as for temporal and spatial variation in demographic rates. Multiple runs of the model enabled us to construct probability distributions, both for the population sizes in the first 2 years following cyclic lows in the grouse populations and for the number of years to recommencement of driven grouse shooting. The model results quantified the extent to which high densities of harriers pose challenges for grouse management. At harrier densities of or below 0·025 km2, harrier impacts were predicted to reduce autumn grouse densities by <10%, suggesting that a quota scheme could theoretically support coexistence between grouse shooting and harrier conservation. Synthesis and applications. Conflict management requires dialogue between conflicting parties and can benefit from objective inputs from scientists using an agreed evidence base and transparent derivation of relevant information from that evidence base. By discussing the principles of model development and eligibility of data sets with a stakeholder group in advance of producing model results, we achieved buy‐in from all parties involved. Our model informs the debate: whether this additional information will lead to the development and testing of a quota system in practice remains to be seen.